Negotiating Desire: A Lacanian Reading of Chris Abani’s Becoming Abigail - Emmanuel Asika, Ikechukwu; Akabuike, Ifeoma Grace; Gladys Obi, Nwakaego; Lauretta, Chinyeaka (Journal of Neonatal Surgery, 2025)
This paper deploys Lacan’s theory of desire in reading Chris Abani’s Becoming Abigail. Jacques Lacan, in his vested interest in human psychology, developed deep psychological insights influential not just in understanding the components of human psychology but in critical engagement with literature. One of the highpoints of Lacan’s postulations is his theory of desire. In the theory, he projects the knowledge of Ate with which he seeks to explain the desires and psychological drives of the human mind which often leads to a tragedy. Lacan, in the theory, argues that it is not harmatia that is usually the source of the tragic end of a hero but the Ate– the desire, a zone of second death closely linked to Freud’s Thanatos with which he seeks to give several of Freud’s concepts– a Lacanian conclusion. Deploying this theorization of the desire–Ate, the study demonstrates how the tragic atmosphere in Chris Abani’s Becoming Abigail, experiential in the actions of some of the characters in the novel, is piloted not merely by their tragic flaws but by a psychological yearning for tranquility that is found in death– an affirmation of Ate central in Lacan’s theorization. The paper concludes that the awareness of Ate provides a gateway to understanding human desires and motivations and in controlling and engaging them.